People with disabilities on tribal lands : education, health care, vocational rehabilitation, and independent living. - National Council on Disability (U.S.) (Washington, DC (1331 F St., NW, Ste. 850, Washington 20004) : National Council on Disability, 2003)
"August 1, 2003." Shipping list no.: 2003-0248-P. Cover title. Includes bibliographical references. Mode of access: Internet.